Investments, value of output and trade in livestock sector in India: Pre- and post-WTO era - Dastagiri, M B (The Indian Journal of Animal Sciences, 2011)
The domestic and international economic environment is changing rapidly since implementation of WTO agreements and rules by the early 1990’s. The livestock sector is a promising sector and is playing vital role in agricultural economy. The 11th Five Year Plan (2007–12) and National Agricultural Policy (2000) have given much focus on livestock sector to achieve the target growth rate of 4% in the agricultural sector. However, there is a decline in public investment in both agriculture and livestock. There is a notion that livestock is a neglected sector in terms of investment and its distribution is also skewed. The investment in livestock sector was not substantial compared to its value of output. India has a tremendous potential to produce and export livestock and its products in the present liberalized era. The present study has analyzed the growth rates and trends of government investment on animal husbandry and dairy, livestock GDP and trade during pre- and post-WTO era. The results showed that Government investment on animal husbandry and dairying (GEAHD) has increased oneand half-fold in real terms during pre-WTO period particularly in 80’s compared to 70’s. But the same trend was not followed during 90’s onwards. During post WTO period, from 90’s onwards, it is declining which is a serious concern and needs policy attention. Its overall annual compound growth rate as well as in 80’s and 90’s decades, and during WTO regime was negative but value of output growth rates during these periods increased varied from 4 to 5%, which is paradoxical. Milk group has contributed major share in livestock GDP during 1970–2004. The growth rate in livestock GDP is steady at about 4%. This study showed that meat products constituted the largest share in the total exports. India had been the next exporter of meat products from 1981 to 2001, but in dairy producrs net exporter in the post WTO period. India remained net importer of animal fats and hides and skins. These reults have important policy implications. Indian Government should increase government spending to increase livestock production and which in turn will increase livestock export.